Frequency of chemoradiotherapy-induced mucositis and related risk factors in patients with the head-and-neck cancers: A survey in the North of Iran - Hamid Saeidi Saedi; Hooshang Gerami; Soheil Soltanipour; Ali Faghih Habibi; Mahmood Mirhosseyni; Sina Montazeri; Shadman Nemati (Wolters Kluwer Medknow Publications, 2019)
Background: In this study, we aimed at evaluating the frequency of chemoradiotherapy-induced mucositis (CIM, RIM) and its related risk factors in patients with the head-and-neck cancers (HNCs). Materials and Methods: In this cross-sectional prospective descriptive study, we evaluated a total of 54 HNCs patients referred to the Oncology Chemoradiotherapy Department of Razi and Amiralmomenin University Hospitals of Rasht, for site and grade (WHO classification) of CIM/RIM, based on their demographic features and possible risk factors. SPSS software version 18 and statistical tests (i.e., Fisher's exact test) were used, and the level of significance was considered as P < 0.05. Results: Finally, patients enrolled in the study were 34 men and 20 women (40-72-year-old), of which 43 cases (79.6%) showed signs and symptoms of CIM/RIM (mostly aged 60-69-year-old). Grade 2 mucositis was the most frequent type (18 cases: 33.3%) and mouth floor was the most common site of CIM/RIM (15 patients: 34.9%). Age (P = 0.023), gender (P = 0.012), and the severity of pain (P = 0.018) were significantly related to mucositis in patients with HNCs who underwent chemotherapy or radiotherapy. Conclusion: Mucositis, especially in the oral cavity, is a common complication of chemoradiotherapy in HNCs patients. Age, gender, and the severity of pain are significantly associated with the frequency of CIM/RIM.